La causalidad del Motor inmóvil según Aristóteles - Berti, Enrico (Sapientia, 2012)
Against the traditional interpretation, the article maintains that the unmoved Mover for Aristotle is not a final cause, but he is rather an efficient cause of the heaven’s motion, as it results from Metaph. XII 6. The unmoved Mover is a final cause only in the sense that he is the end of his own activity, as it is proved from the fact that his activity is a pleasure (Metaph. XII 7). The traditional interpretation, following which the heaven moves itself for the love of the unmoved Mover, trying to imitate his immobility trough the circular motion, derives from the attempt to reconcile Aristotle’s thought with the Platonic conception of imitation of the intelligible by the sensible reality. The unmoved Mover is the end of man only in the sense that he is the object of the knowledge in which the human happiness consists (Eud. Eth. VIII 3).